Monoclonal immunoglobulin mediates complement activation in monoclonal gammopathy associated-C3 glomerulonephritis - Li, Lin-Lin (BMC Nephrol, 2019)
BACKGROUND: C3 glomerulonephritis (C3GN) is a rare disease caused by inherited or acquired complement alternative pathway (CAP) dysregulation, which could also be secondary to monoclonal gammopathy of undetermined significance (MGUS). Herein, we described a patient presenting with C3GN and monoclonal gammopathy, and the pathogenic association between the two diseases was further explored in vitro. CASE PRESENTATION: A 76-year-old Chinese man presented with low serum C3 level, haematuria and nephrotic syndrome, and experienced rapid worsening of renal function over a period of 10 months. His serum and urine immunofixation electrophoresis both revealed a monoclonal IgGλ. A bone marrow puncture showed plasma cell dyscrasias with the highest plasma cell count of 5.25%. Kidney biopsy showed the presence of C3 glomerulonephritis, with exclusive deposits of C3 visible on immunofluorescence, a membranoproliferative pattern on light microscopy and electron dense deposits in sub-epithelial, intramembranous, sub-endothelial and mesangial regions by electron microscopy. The patient was positive for C3 nephritic factor (C3NeF) activity and anti-CFH autoantibodies, and all became negative during disease remission. The anti-CFH autoantibodies purified from the patient’s plasma exchange fluids were proven to be a monoclonal IgGλ, and could inhibit CFH binding to C3b and accelerate the formation of C3 convertase indirectly by interfering with the formation-impeding activity of CFH. No deficiency of candidate genes, especially variants in CFH, was detected in our patient. Based on the pathological and laboratory findings, the diagnosis of monoclonal gammopathy of renal significance (MGRS)-associated C3GN was finally made. CONCLUSIONS: This is the first demonstration that intact monoclonal immunoglobulin (IgGλ) could act as an anti-CFH antibody and lead to MGRS-associated C3GN by activating the CAP.